PARTICLE SWARM OPTIMIZATION BASED INVENTORY POLICY FOR WHOLESALE BUSINESS IN DEVS BASED MEDICINE SUPPLY CHAIN - Jaekwon, Kim (International Journal of Industrial Engineering: Theory, Applications and Practice, 2017)
Inventory policy of medicine wholesaler is very important issue because a medicine supply chain is directly related to human’s lives. FOQ (Fixed Order Quantity), POQ (Periodic Order Quantity, (s,S) and (R,S) of inventory policies is widely used to manage the medicine stock in the present trend. However, effective management of medicine inventory is a difficult problem due to characteristics of the medicine. We proposed PSO-(s) (Particle Swarm Optimization) based inventory policy for wholesale dealers in medicine supply chain. We build a DEVS (Discrete event system specification)-based modeling to implement a virtual medicine supply chain. We also simulate the designed model to measure a performance of management policies. The proposed PSO-(s) determines optimal volume of products at the specific order time by using current stocks. Simulation results demonstrate that PSO-(s) is an efficient method for wholesaler’s inventory management and medicine supply chain.